Ethnodevelopment and territorial management in patagonian tourist context - Impemba, Marcelo (Cooperativismo & Desarrollo, 2021)
Themes and content expressed in the present work are the result of different research projects and university extension programs, in which they have addressed the development of tourism and its socio-cultural and economic impact on Mapuche communities of the region andina patagónica of Argentina.To approach tourism, space and historically contextualized in relation to indigenous communities, represents a vast field of research on those changes in environmental, territorial and their productive practices conditions.Among the axles that have guided the field work, you can highlight the study of their vindictive actions, the territorial changes, and the representations and stigmatization of the rest of society, from the perspective of the ethnodevelopment of tourism.
Keywords: territory; tourist development; inter-ethnic relations; tourist field; mapuche communities